1998
DOI: 10.1177/016224399802300302
|View full text |Cite
|
Sign up to set email alerts
|

Untangling Context: Understanding a University Laboratory in the Commercial World

Abstract: The past twenty years have been an incredibly productive period in science studies. Still, because recent work in science studies puts a spotlight on agency and enabling situations, many practitioners in the field ignore, underplay, or dismiss the possibility that historically established, structurally stable attributes of the world may systemically shape practice at the laboratory level. This article questions this general position. Drawing on data from a participant observation study of a university biology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 44 publications
(31 reference statements)
0
47
0
Order By: Relevance
“…48 Finally, beyond its usefulness in this specific case, this approach to studying institution-building may have the potential to speak to STS more generally. In recent years a number of scholars have been arguing that STS should pay closer attention to the effects of political-economic and organizational factors (Kleinman, 1998, power and resources (Klein & Kleinman, 2002;Goven, 2006), formal organizations (Vaughan, 1999), institutions, networks, and power (Frickel & Moore, 2006), and political economy (Mirowski & Sent, 2007) on science and technology. We might call these approaches broadly 'structural', in their emphasis on the way that social conditions external to the individual affect both what individuals can do and what they choose to do.…”
Section: What Does An Institutional Approach Gain Us?mentioning
confidence: 99%
See 1 more Smart Citation
“…48 Finally, beyond its usefulness in this specific case, this approach to studying institution-building may have the potential to speak to STS more generally. In recent years a number of scholars have been arguing that STS should pay closer attention to the effects of political-economic and organizational factors (Kleinman, 1998, power and resources (Klein & Kleinman, 2002;Goven, 2006), formal organizations (Vaughan, 1999), institutions, networks, and power (Frickel & Moore, 2006), and political economy (Mirowski & Sent, 2007) on science and technology. We might call these approaches broadly 'structural', in their emphasis on the way that social conditions external to the individual affect both what individuals can do and what they choose to do.…”
Section: What Does An Institutional Approach Gain Us?mentioning
confidence: 99%
“…The study of institution-building fits with such a trend. Empirical studies written from such a perspective are still fairly few in number, and to date most have focused on the impact of structural conditions on science; that is, how factors like organizations, politics, and economics shape the practice of science (Kleinman, 1998Vaughan, 1999;Hyysalo, 2006;Parthasarathy, 2005). But this paper, which tries to understand the creation of a practice external to the laboratory that shapes what happens within it, focuses on a slightly different piece of the puzzle: how one of those structures itself is produced.…”
Section: What Does An Institutional Approach Gain Us?mentioning
confidence: 99%
“…Attention to the primacy of subjective experience is an epistemic imperative (Kleinman 1998(Kleinman , 2007Jenkins 2015a) for the illumination of what matters most: people's own experience defined in their own terms as irreducible source of knowledge in the social and health sciences, including medical humanities. In the present instance, critical questions concern these youths' subjective experiences and meanings of anxiety.…”
Section: Subjective Experiences Of Severe Anxiety: Two Case Illustratmentioning
confidence: 99%
“…There is plenty of good research in the field of STS that shows the myriad ways capitalism's insistence on imposing factory-like efficiencies impact knowledge production and circulation. For example, Daniel Kleinman (1998) has shown that the standardization of lab equipment and commercially available chemicals (in Kleinman's case a pesticide) can have a direct effect on the direction of research and the definition of a successful experiment.…”
Section: The Autopsy: a Reason That Garden Cities Failedmentioning
confidence: 99%